FARM SIZE AS A FACTOR OF EMLOYMENT AND INCOME OF MEMBERS OF FAMILY FARMS - Petar Munćan; Dragica Božić (Ekonomika Poljoprivrede (1979), 2017)
Based on data collected through a survey of 35 family farms in Vojvodina, specialized in the market-oriented agricultural production, the interdependence of the size of family farm and structure of feld crop production was studied, and its impact on the employment of permanent members actively employed in agriculture and their income. It was found that with an increase of farm size from 20 to 100 ha, the utilization of the available fund of working hours of active members increases by almost 2 times. In addition, with an increase in the size of the farm and increase in the share of industrial crops in the structure of feld crop production, income per active member of the family household employed in agriculture also exhibits a tendency to increase. Income per active member, on the farms of 50-100 ha, is 3.6 times higher than the income generated on farms of 10-20 ha in size.